A Study on the Potential of Active Constituent from Senna spectabilis in Treating Leishmania major Infection - IFNM, Institut Farmaseutikal & Nutraseutikal Malaysia (2017)
Leishmaniasis affects millions of people each year. It consists of a group of tropical infections that are effecting human populations in mainly low-income countries. Visceral Leishmaniasis (VL) and Cutaneous Leishmaniasis (CL) are the main forms of Leishmaniasis which cause mortality, chronic disability and poverty. Leishmanasis is among three of most neglected diseases in the world, together with Human African Trypanosomiasis (HAT) and Chagas’ disease. These diseases are termed as neglected diseases because they are receiving very limited press attention as well as research funding as compared to HIV/AIDS, tuberculosis and malaria. In 2003, Drugs for Neglected Diseases Initiative (DNDi) which is a non-profit drug R&D agency focusing on developing new treatments for neglected diseases was established